Structural Characterization of Boride Layer on Boronized Ductile Irons - Yılmaz, Fevzi; Şen, Uğur; Şen, Saduman (Elsevier, 2004)
In this work, some surface properties of ductile irons were improved by a them1o-chemical boronizing process. Boronizing wasperfom1ed in a slurry salt bath consisting of borax, boric acid and ferro-silicon at 850 and 950 °C for 2- 8 h. Three different ductile irons namely GGG 50, GGG 60 and GGG 80 were used to investigate the surface properties and performance. Structural characterization of boride layer fonned on the surface of ductile irons was carried out by using optical microscopy, scanning electron microscopy back scattered electron image, electron microprobe and X-ray diffraction (XRD) analysis. The hardness measurements of boride layers were conducted under 100 g loads by using Vickers microhardness indenter. Structural analysis studies showed that carbon and silicon were concentrated between boride layers and substrate. When copper concentration of ductile irons increases, the carbon and silicon enriched region between boride layer and substrate decreases. XRD analysis showed that borided GGG 50 and GGG 60 ductile irons have FeB and Fe2B phases. However, borided GGG 80 ductile iron at 850 °C has only Fe2B phase at the experimented range of time. Therefore, the hardness of boride layer fonned on the surface of GGG 80 ductile iron is lower than that of GGG 50 and GGG 60 ductile irons
Keywords: Boronizing; Ductile iron; Coating; Hardness